Going Deep into Synaptic Vesicle Machinery Genes and Migraine Susceptibility – A Case‐Control Association Study. Issue 10 (26th September 2020) - Quintas, Marlene; Neto, João Luís; Sequeiros, Jorge; Sousa, Alda; Pereira‐Monteiro, José; Lemos, Carolina; Alonso, Isabel
Abstract : Objective: A number of observations, including among our study population, have implicated variants in the syntaxin‐1A, a component of the synaptic vesicles, in migraine susceptibility. Therefore, we hypothesize that variants in other components of the vesicle machinery are involved in migraine. Background: Migraine is a common and complex neurologic disorder that affects approximately 15‐18% of the general population. The exact cause of migraine is unknown; however, genetic studies have made possible substantial progress toward the identification of underlying molecular pathways. Neurotransmitters have been for long considered to have a key role in migraine pathophysiology; so we investigated common variants in genes involved in the synaptic vesicle machinery and their impact in migraine susceptibility. Methods: We performed a case‐control study comprising 188 unrelated patients with headache and 286 healthy controls in a population from the north of Portugal. Benefiting from the presence of linkage disequilibrium, we selected and genotyped 119 tagging single‐nucleotide polymorphisms in 18 genes. Results: We found significant associations between single‐nucleotide variants and migraine in 7 genes, SYN1, SYN2, SNAP25, VAMP2, STXBP1, STXBP5, and UNC13A, either conferring an increased risk or protection of migraine. Due to SYN1 X‐chromosomal location, we performed the statistical analysis separated by gender and, in the female group, the C allele of rs5906435 increased the risk for migraine susceptibility ( P = .021; OR = 1.69; 95% CI: 1.21‐2.34). In contrast, the TT genotype of the same variant emerged as a potential protective factor ( P = .003; OR = 0.45; 95% CI: 0.27‐0.74). The SYN2 analysis supported the rs3773364's G allele ( P = .014) as a risk factor for migraine, and although not statistically significant after correction, the AG genotype ( P = .006; OR = 1.86; 95% CI: 1.20‐2.90) reinforced the allelic findings. Additionally, we found the SNAP25 ‐rs363039's CT genotype ( P = .001; OR = 2.14; 95% CI: 1.36‐3.34), the STXBP5 ‐rs1765028's T allele ( P = .041; OR = 1.46; 95% CI: 1.13‐1.90), and the UNC13B ‐rs7851161's TT genotype ( P = .001; OR = 2.14; 95% CI: 1.36‐3.34) as statistically significant risk factors for migraine liability. VAMP2 ‐rs1150's G allele revealed a risk association to migraine, not statistically significant after correction ( P = .068). Additionally, we found haplotypes in SYN1, SYN2, STXBP1, and UNC13B to be associated with migraine. Conclusions: Overall, this study provides a new insight into migraine liability, identifying possible starting points for functional studies.